Hymns and Psalms (UK The Methodist Publishing House, 1986)
A Methodist and Ecumenical Hymn Book
Contains 888 hymns with music
"The Methodist Conference meeting in Plymouth, 1982, authorised this hymn book for use in all Methodist churches in the Connexion, and in succession to the 1933 Hymn Book." . 1 score
Prepared by representatives of the British Methodist Conference and by members of the Baptist Union, Churches of Christ, Church of England, Congregational Federation, Methodist Church in Ireland, United Reformed Church, and the Wesleyan Reform Union
On spine: Hymns & psalms. Words and music edition
Keywords: Liturgy (3GddGghJ GdWbSj (B- (3GddjJhQLjGs; Theology -- Hymns; Methodist Church; Hymns, English